Intentional release of tropical aquarium fishes? Orange chromide (Pseudetroplus maculatus) found in Finland - Granroth, Janne; Pihlström, Henry; Kuningas, Sanna (Societas pro fauna et flora Fennica, 2026)
Ornamental fish keeping is a popular hobby around the world, including Finland. Occasionally, aquarium fish end up in the wild either accidentally or via intentional release. Most such escapees undoubtedly perish quickly, but some may survive long enough to have a negative impact on the native fauna. Impacts of alien species on native fish may include predation, competition, hybridization, and the spread of diseases. These effects are especially noticeable if the alien species manage to form self-sustaining populations. While anecdotal reports of exotic aquarium fish encountered in the wild have been published from Finland and other European countries, the true scale of this phenomenon is difficult to establish. Here, we report the discovery of two individuals of the South Asia-native orange chromide (Pseudetroplus maculatus, Cichlidae, Cichliformes) that were discovered freshly dead on a riverbank in southern Finland. We discuss the possible biological risks associated with the release of exotic aquarium fishes in a Finnish context.
Keywords: biological risks; exotic aquarium fishes; release